The Effect of Education on the Utilization of Hypnotherapy in Antenatal and Intrapartum Care on Midwives’ Knowledge - Rima Wirenviona; Fani Syinthia Rahmi; Fitri Ramadhaniati; Nurul Fatimah Susanti; Nurul Jannatul Wahidah (Open Access Health Scientific Journal, 2026)
Background: Hypnotherapy is a non-pharmacological approach that has increasingly been applied in midwifery care, particularly in antenatal and intrapartum services, to assist pregnant women in managing anxiety and pain and to enhance comfort during childbirth. However, the utilization of hypnotherapy in health services remains limited, partly due to insufficient knowledge and understanding among midwives regarding its concepts and applications.Methods: This study employed a quasi-experimental design with a one-group pretest–posttest approach. The study was conducted among midwives providing antenatal and intrapartum care in healthcare facilities. Samples were selected using a total sampling technique. Data were collected using a questionnaire measuring knowledge related to the utilization of hypnotherapy. Data analysis was conducted using univariate and bivariate statistical analyses.Results: The findings demonstrated an increase in the mean knowledge scores of midwives after receiving education on hypnotherapy utilization compared to before the intervention. Statistically, education on hypnotherapy utilization had a significant effect on improving midwives’ knowledge.Conclusion: Education on the utilization of hypnotherapy in antenatal and intrapartum care significantly improves midwives’ knowledge. These findings are expected to serve as a foundation for the development of training programs and the implementation of hypnotherapy as part of comprehensive midwifery care.